2018
DOI: 10.2460/javma.253.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of factors associated with surgical site infection in dogs following tibial plateau leveling osteotomy

Abstract: OBJECTIVE To identify risk factors associated with surgical site infection (SSI) in dogs following tibial plateau leveling osteotomy (TPLO). DESIGN Retrospective cohort study. ANIMALS 320 dogs that underwent unilateral or bilateral TPLO (n = 405 procedures) between 2007 and 2015 and were reexamined by a veterinarian at least once ≥ 8 weeks after the procedure. PROCEDURES Data were extracted from medical records regarding signalment, TPLO procedure details, medical history of dermatitis, and SSI status. Logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 34 publications
2
30
1
Order By: Relevance
“…Increased anaesthetic duration, surgical time, method of skin closure, meniscectomy and surgeon experience have been significantly associated with SSI in previous veterinary orthopaedic studies [16][17][18][19][20][21][22] but none of these variables were found to be significantly associated with development of SSI in ours and previous studies. 14,21,33,49 Human CDC guidelines for classification of SSI have recently been updated to include infections developing up to 90 days after surgery where an implant is used. 23 No veterinary-specific guidelines are established and therefore veterinary literature often cites previous CDC guidelines for SSI investigations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased anaesthetic duration, surgical time, method of skin closure, meniscectomy and surgeon experience have been significantly associated with SSI in previous veterinary orthopaedic studies [16][17][18][19][20][21][22] but none of these variables were found to be significantly associated with development of SSI in ours and previous studies. 14,21,33,49 Human CDC guidelines for classification of SSI have recently been updated to include infections developing up to 90 days after surgery where an implant is used. 23 No veterinary-specific guidelines are established and therefore veterinary literature often cites previous CDC guidelines for SSI investigations.…”
Section: Discussionmentioning
confidence: 99%
“…9,[11][12][13] Surgical site infection (SSI) rates following surgical management of cranial cruciate ligament rupture range from 3 to 26%. [14][15][16][17][18][19][20][21][22] Two previous studies examining arthrotomy and lateral fabellotibial suture for the management of cranial cruciate ligament rupture reported infection rates of 3.9 to 4.2%. 12,20 Meniscectomy, surgeon experience, breed, postoperative antibiotic medications, implant selection, anaesthetic and surgical times, bodyweight and use of skin staples have all been implicated as risk factors for SSI following stifle surgery in dogs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The remaining 69% (9/13) of studies provided data on postoperative antibiotic use as a secondary outcome measurement (Table 1B). 6,[9][10][11][22][23][24]28,29 All studies were retrospective, with mOLE classification of either 4b or 4c. These studies provided evaluation of 3227 TPLO procedures, and publication years ranged from 2010 to 2019.…”
Section: Manuscript Reviewmentioning
confidence: 99%
“…Contradictory findings, however, have been reported. Several reports of recent studies involving dogs undergoing TPLO have described a reduced risk of postoperative infection with the use of postoperative antibiotic therapy, while other reports have described findings that postoperative antibiotic therapy did not result in a significant reduction in SSI . However, the only two studies in which dogs weighing >50 kg were assessed provided evidence of a protective effect of the use of postoperative antimicrobial treatment .…”
Section: Discussionmentioning
confidence: 99%